Modern methods in evaluating the teaching performance of the university professor between the hoped and the reality of implementation in Algeria. - Smaili, Mahmoud; Benamara, Saida; Naim, BENAMARA (Milev Journal of Research and Studies, 2019)
The importance of evaluating job performance is increased by increasing awareness of what it can offer for planning, organizing, training, and recruitment in any administrative organization or educational institution. Where it is considered one of the most important activities and processes related to human resources management, but it still does not receive enough attention. There is considerable controversy and doubt, especially the evaluation of academic performance of faculty members in general, and teaching performance in particular, we find it mostly personal and according to individual jurisprudence and is still far from objective orthodontic treatments to detect and address deficiencies, in addition to many complaints from students about poor teaching performance of some faculty members, some of whom have left their lectures, or performed in a formal manner that does not take into account what should be the effective teaching performance. Accordingly, this study examines the possibility of adopting and applying modern methods in evaluating the teaching performance of the university professor in Algeria.